ICC is on trial in Africa - (:unkn) unknown (Daily Nation, 2015)
The relationship between Kenya and the ICC is not an international relationship in the traditional sense. It is rather a devolved relationship. We could brand the ICC mediocre, unfair and irrelevant; a Western tool for manipulation, but we freely signed and ratified the Rome Statute. Withdrawing from the ICC now in the midst of the process would be a misadvised step, legally and politically.
Newspaper article published in Daily Nation on June 13, 2013
The relationship between Kenya and the ICC is not an international relationship in the traditional sense. It is rather a devolved relationship. We could brand the ICC mediocre, unfair and irrelevant; a Western tool for manipulation, but we freely signed and ratified the Rome Statute. Withdrawing from the ICC now in the midst of the process would be a misadvised step, legally and politically
Keywords: ICC; Africa